Metallurgical investigation of wire breakage of tyre bead grade. (October 2015) - Palit, Piyas; Das, Souvik; Mathur, Jitendra
Highlights: Tyre bead grade wire is used for tyre making application. During tyre making operation at tyre manufacturer company, wire failed frequently in brittle mode. Crow feet like defects including button like surface abnormalities were also observed. The analysis revealed that, surface martensite was formed and it caused the final breakage. Abstract: Tyre bead grade wire is used for tyre making application. The wire is used as reinforcement inside the polymer of tyre. The wire is available in different size/section such as 1.6–0.80 mm thin Cu coated wire. During tyre making operation at tyre manufacturer company, wire failed frequently. In this present study, different broken/defective wire samples were collected from wire mill for detailed investigation of the defect. The natures of the defects were localized and similar in nature. The fracture surface was of finger nail type. Crow feet like defects including button like surface abnormalities were also observed on the broken wire samples. The defect was studied at different directions under microscope. Different advanced metallographic techniques have been used for detail investigation. The analysis revealed that, white layer of surface martensite was formed and it caused the final breakage of wire. In this present study we have also discussed about the possible reason for the formation of such kind of surface martensite (hard-phase).